2010
DOI: 10.1002/eji.201040688
|View full text |Cite
|
Sign up to set email alerts
|

Functional involvement of Daxx in gp130‐mediated cell growth and survival in BaF3 cells

Abstract: Death domain-associated protein (Daxx) is a multifunctional protein that modulates both cell death and transcription. Several recent studies have indicated that Daxx is a mediator of lymphocyte death and/or growth suppression, although the detailed mechanism is unclear. Previously, we reported that Daxx suppresses IL-6 family cytokine-induced gene expression by interacting with STAT3. STAT3 is important for the growth and survival of lymphocytes; therefore, we here examined the role of Daxx in the gp130/STAT3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…An interleukin (IL)-3-dependent murine pro-B cell line, BaF-G133, was maintained in RPMI 1640 medium supplemented with 10% FCS with 10% of WEHI-3B conditioned medium as a source of IL-3 (25,26). ARL3-knockdown HeLa cell lines (cell lines 2-4 and 2-10) were established by transduction with pGPU6/GFP/Neo vector (Shanghai GenePharm, Shanghai, China) bearing short hairpin RNA (shRNA) targeting ARL3 (5Ј-GCAGCTTGCATCTGAA-GACAT-3Ј) and then selected with G418 (1 mg/ml; Sigma) (27).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An interleukin (IL)-3-dependent murine pro-B cell line, BaF-G133, was maintained in RPMI 1640 medium supplemented with 10% FCS with 10% of WEHI-3B conditioned medium as a source of IL-3 (25,26). ARL3-knockdown HeLa cell lines (cell lines 2-4 and 2-10) were established by transduction with pGPU6/GFP/Neo vector (Shanghai GenePharm, Shanghai, China) bearing short hairpin RNA (shRNA) targeting ARL3 (5Ј-GCAGCTTGCATCTGAA-GACAT-3Ј) and then selected with G418 (1 mg/ml; Sigma) (27).…”
Section: Methodsmentioning
confidence: 99%
“…Cell Proliferation Assay-The numbers of viable BaF-G133 cells after the indicated treatments were measured using a WST-8 (2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium, monosodium salt) assay (cell counting kit-8; Wako Pure Chemicals) (26). Briefly, 10 l of WST-8 solution was added to the cells in each well and incubated for 2 h. The absorbances were measured at a test wavelength of 450 nm and a reference wavelength of 595 nm using a microplate reader (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, Daxx 501 to 625-induced apoptosis is mediated through the ASK1-MEK-JNK/p38-Bim-Bax-dependent caspase pathway. Muromoto et al (2010) found out that knock down of Daxx attenuated lactate dehydrogenase leakage from cells, indicating that Daxx positively regulates cell death during gp130/STAT3-mediated cell proliferation.…”
Section: Daxx and Proapoptosismentioning
confidence: 97%
“…Muromoto et al (2010) found out that Daxx suppresses the gp130/STAT3-dependent cell growth and that Daxx endogenously interacts with STAT3 and inhibits the DNAbinding activity of STAT3. Moreover, small-interfering RNA-mediated knockdown of Daxx enhanced the expression of STAT3-target genes and accelerated the STAT3-mediated cell cycle progression.…”
Section: Daxx As a Transcriptional Regulatormentioning
confidence: 99%